Motility of the jejunum after proctocolectomy and ileal pouch anastomosis. Issue 3 (March 1989) - Chaussade, S; Merite, F; Hautefeuille, M; Valleur, P; Hautefeuille, P; Couturier, D
Abstract : Proctocolectomy with ileal pouch anastomosis could modify motility of the small intestine through two mechanisms: obstruction or bacterial overgrowth. Motility of the jejunum was measured in 11 patients with ileoanal anastomosis six (n = 6), or 12 (n = 5) months after closure of the loop ileostomy. Manometric recording from the jejunum were made during fasting (four hours) and after a liquid meal (one hour). These findings were compared with those of six healthy volunteers. Motor events were classified as follows: migrating motor complex (MMC), propagated contractions, or discrete clustered contractions. All patients were investigated for bacterial overgrowth (D-glucose breath test). Only two patients had bacterial overgrowth. The frequency of MMC remained unchanged after ileo-anal anastomosis (2.83 (0.37)/four hours) compared with normal volunteers (2.81 (0.29)/four hours). During fasting, four patients had numerous propagated contractions in the jejunum. This condition was associated in two with bacterial overgrowth and in two with intubation of the reservoir. Discrete clustered contractions were found in the seven patients studied postprandially (7.6 (2.5)/h), but not in volunteers. These seven patients emptied their pouch spontaneously and bacterial overgrowth was found in only one. As this motility pattern was previously described in partial small intestinal obstruction, it is postulated that discrete clustered contractions could be the consequence of a functional obstruction as a result of anastomosis of the small intestine to the high pressure zone of the anal sphincters.